Bismaleimide-based adhesive composition, cured product, adhesive sheet, and flexible printed wiring board
The bismaleimide adhesive composition with a bismaleimide resin and inorganic filler addresses the adhesion and dielectric challenges of flexible printed wiring boards, offering low transmission loss and high adhesion to copper and polyimide sheets, enhancing the performance of flexible printed wiring boards and related electrical components.
Patent Information
- Application Number
- JP2024190297
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-04-06
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-07-17
AI Technical Summary
Existing insulating materials for flexible printed wiring boards lack sufficient adhesion to smooth copper circuits and have high dielectric constants and loss tangents, leading to significant transmission loss in high-frequency signals.
A bismaleimide adhesive composition containing a bismaleimide resin and an inorganic filler, such as silica, with a specific content range, providing excellent adhesion and low dielectric properties for copper foil and polyimide sheets.
The adhesive composition achieves low dielectric properties, high adhesion, and reduced transmission loss, with a cured product exhibiting low tack, high 5% weight loss temperature, minimal outgassing, and low coefficient of linear expansion, suitable for flexible printed wiring boards and other electrical applications.
Smart Images

Figure 2025010301000001 
Figure 2025010301000002 
Figure 2025010301000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a bismaleimide adhesive composition, a cured product, an adhesive sheet, and a flexible printed wiring board. More specifically, the present invention relates to a novel bismaleimide adhesive composition that has excellent low dielectric properties and also has high adhesion to substrates such as copper foil and polyimide sheet. [Background technology]
[0002] Flexible printed circuit boards (hereinafter referred to as "FPCs") and multilayer wiring boards using FPCs are used in products such as mobile communication devices such as mobile phones and smartphones, as well as their base station equipment, network-related electronic devices such as servers and routers, and large computers.
[0003] In recent years, these products have been using high-frequency electrical signals to transmit and process large volumes of information at high speeds. However, because high-frequency signals are highly susceptible to attenuation, there has been a demand for ways to reduce transmission loss in the above-mentioned FPCs and multilayer wiring boards.
[0004] Transmission loss can be divided into "dielectric loss" that originates from the dielectric, i.e., the insulating material surrounding the conductor (copper circuit), and "conductor loss" that originates from the copper circuit itself, and both need to be suppressed.
[0005] The dielectric loss depends on the frequency and the dielectric constant and dissipation factor of the insulating material surrounding the copper circuit, and the higher the frequency, the lower the dielectric constant and dissipation factor must be.
[0006] On the other hand, conductor loss is caused by the skin effect, i.e., the phenomenon in which the AC current density on the copper circuit surface increases and its resistance increases, and becomes noticeable when the frequency exceeds 1 GHz. The main measure to suppress conductor loss is to smooth the copper circuit surface.
[0007] In order to suppress the dielectric loss, as described above, it is preferable to use a material with a low dielectric constant and low dielectric loss as the insulating material, and specific polyimides have conventionally been used as such materials (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2009-299040 A [Patent Document 2] JP 2014-045076 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, the insulating materials described above have a problem in that they do not have polar groups, i.e., functional groups such as hydroxyl groups, carboxyl groups, and nitrile groups, or have only small amounts of them, making them difficult to adhere to smooth copper circuits. Conversely, materials that have many such functional groups tend to have high dielectric constants and dielectric loss tangents, even if they have high adhesion to smooth copper circuits.
[0010] Therefore, an object of the present invention is to provide a new bismaleimide-based adhesive that has both a low dielectric constant and dielectric tangent (hereinafter, both may be collectively referred to as "dielectric properties") and has good adhesion to copper and polyimide films, particularly to copper with a smooth surface.
[0011] That is, an object of the present invention is to provide a bismaleimide-based adhesive composition that has low dielectric properties and excellent adhesion to substrates such as copper foil, polyimide sheet, etc. Another object of the present invention is to provide a cured product, an adhesive sheet, and a flexible printed wiring board using the bismaleimide-based adhesive composition. [Means for solving the problem]
[0012] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems and found that a bismaleimide-based adhesive composition containing a bismaleimide resin (A) obtained by reacting an aromatic tetracarboxylic acid (a1), a dimer diamine (a2), and maleic anhydride (a3), and an inorganic filler (B), wherein the content of the inorganic filler (B) is within a predetermined range, has excellent low dielectric properties and further has high adhesion to substrates such as copper foil and polyimide sheet, thereby completing the present invention.
[0013] That is, the present invention provides the following inventions. [1] A bismaleimide adhesive composition comprising: a bismaleimide resin (A) obtained by reacting an aromatic tetracarboxylic acid (a1), a dimer diamine (a2), and maleic anhydride (a3); and an inorganic filler (B), wherein the content of the inorganic filler (B) is 5 to 55 mass% based on the total solid content of the adhesive composition. [2] The bismaleimide adhesive composition according to [1] above, wherein the aromatic tetracarboxylic acid (a1) is pyromellitic anhydride or a compound represented by the following general formula (1): [ka] [In formula (1), X represents a single bond or at least one group selected from the following group.] [ka] [3] The bismaleimide adhesive composition according to [1] or [2] above, wherein the dimer diamine (a2) is a compound represented by the following general formula (2) and / or general formula (2'): [ka] [ka] [In formulas (2) and (2'), m, n, p, and q each represent an integer of 1 or more selected such that m+n=6 to 17 and p+q=8 to 19, and the bond shown by a dashed line represents a carbon-carbon single bond or a carbon-carbon double bond. However, when the bond shown by a dashed line is a carbon-carbon double bond, formulas (2) and (2') have a structure in which the number of hydrogen atoms bonded to each carbon atom constituting the carbon-carbon double bond is reduced by one from the number shown in formulas (2) and (2')] [4] The bismaleimide adhesive composition according to any one of the above [1] to [3], wherein the bismaleimide resin (A) has a weight average molecular weight of 3,000 to 25,000. [5] The bismaleimide adhesive composition according to any one of [1] to [4] above, wherein the inorganic filler is silica. [6] The bismaleimide adhesive composition according to any one of the above [1] to [5], further comprising a polymerization initiator (D). [7] The bismaleimide adhesive composition according to [6] above, wherein the polymerization initiator (D) is at least one selected from the group consisting of organic peroxides, imidazole compounds, phosphine compounds, and phosphonium salt compounds. [8] The bismaleimide adhesive composition according to any one of the above [1] to [7], wherein the inorganic filler (B) has an average particle size of 100 nm to 10 μm. [9] The bismaleimide adhesive composition according to any one of the above [1] to [8], wherein the inorganic filler (B) has an average particle size of 200 nm to 1.0 μm.
[10] The bismaleimide-based adhesive composition according to any one of [1] to [9] above, wherein the content of the inorganic filler (B) is 5 to 25 mass % based on the total solid content of the adhesive composition.
[11] A cured product obtained by curing the bismaleimide adhesive composition according to any one of [1] to
[10] above.
[12] An adhesive sheet obtainable by applying the bismaleimide-based adhesive composition according to any one of the above [1] to
[10] to a sheet substrate and drying it.
[13] A laminate obtained by further thermocompression bonding a sheet substrate to the adhesive surface of the adhesive sheet described in
[12] above.
[14] A laminate obtained by further heating the laminate described in
[13] above.
[15] A flexible printed wiring board comprising the laminate according to
[14] above. Effect of the Invention
[0014] The present invention can provide a bismaleimide-based adhesive composition that has low dielectric properties and excellent adhesion to substrates such as copper foil and polyimide sheet, as well as a cured product, adhesive sheet, and flexible printed wiring board using the same.
[0015] The adhesive composition of the present invention not only has excellent low dielectric properties in the high frequency band, but also has excellent adhesion to substrates such as copper foils and polyimide sheets. In addition, the cured product (adhesive layer) obtained from the adhesive composition has low tack, a high 5% weight loss temperature, little outgassing, and a low coefficient of linear expansion (CTE), and is therefore useful not only as an adhesive used in the manufacture of printed circuit boards (build-up boards, flexible printed wiring boards, etc.) and copper-clad boards for flexible printed wiring boards, but also as an electrical insulating material such as a semiconductor interlayer material, a coating agent, a resist ink, and a conductive paste. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described in detail.
[0017] <Bismaleimide-based adhesive composition> The bismaleimide adhesive composition of this embodiment contains a bismaleimide resin (A) (hereinafter also referred to as "component (A)") obtained by reacting aromatic tetracarboxylic acids (a1) (hereinafter also referred to as "component (a1)"), dimer diamine (a2) (hereinafter also referred to as "component (a2)"), and maleic anhydride (a3) (hereinafter also referred to as "component (a3)"), and an inorganic filler (B) (hereinafter also referred to as "component (B)"). The bismaleimide adhesive composition of this embodiment may further contain an organic solvent (C) (hereinafter also referred to as "component (C)"). The bismaleimide adhesive composition of this embodiment may further contain a polymerization initiator (D) (hereinafter also referred to as "component (D)").
[0018] (Component (A): Bismaleimide resin) The component (A) can be obtained by reacting the components (a1), (a2), and (a3).
[0019] As the component (a1), any known polyimide raw material can be used, specifically, pyromellitic anhydride and a compound represented by the following general formula (1) can be used. [ka] [In formula (1), X represents a single bond or at least one group selected from the following group.] [ka]
[0020] Examples of the compound represented by formula (1) include 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 2,3,3',4'-biphenyl tetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride, 2,3,3',4'-diphenyl sulfone tetracarboxylic dianhydride, 2,2-bis(3,3' ,4,4'-tetracarboxyphenyl)tetrafluoropropane dianhydride, 2,2'-bis(3,4-dicarboxyphenoxyphenyl)sulfone dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, butane-1,2,3,4-tetracarboxylic acid, 2,3,5-tricarboxycyclopentylacetic anhydride, 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, etc. These can be used alone or in combination of two or more.
[0021] The component (a2) is a compound derived from a dimer acid, which is a dimer of an unsaturated fatty acid such as oleic acid, as described in, for example, JP-A-9-12712. In this embodiment, any known dimer diamine can be used without particular limitation, but for example, those represented by the following general formula (2) and / or general formula (2') are preferred.
[0022] [ka] [ka] [In formulas (2) and (2'), m, n, p, and q each represent an integer of 1 or more selected such that m+n=6 to 17 and p+q=8 to 19, and the bond shown by a dashed line represents a carbon-carbon single bond or a carbon-carbon double bond. However, when the bond shown by a dashed line is a carbon-carbon double bond, formulas (2) and (2') have a structure in which the number of hydrogen atoms bonded to each carbon atom constituting the carbon-carbon double bond is reduced by one from the number shown in formulas (2) and (2')]
[0023] As the dimer diamine, from the viewpoints of solubility in organic solvents, heat resistance, heat-resistant adhesion, low viscosity, etc., the compound represented by the above general formula (2') is preferred, and the compound represented by the following formula (3) is particularly preferred. [ka]
[0024] Commercially available dimer diamines include, for example, PRIAMINE 1075 and PRIAMINE 1074 (both manufactured by Croda Japan Co., Ltd.) These may be used alone or in combination of two or more.
[0025] The (A) component can be produced by various known methods. For example, first, the (a1) component and the (a2) component are polyaddition reacted at about 60 to 120°C, preferably 70 to 90°C, for about 0.1 to 2 hours, preferably 0.1 to 1.0 hours. The resulting polyaddition product is then subjected to an imidization reaction, i.e., a dehydration ring-closing reaction, at about 80 to 250°C, preferably 100 to 200°C, for about 0.5 to 30 hours, preferably 0.5 to 10 hours. The product obtained by the dehydration ring-closing reaction is then subjected to a maleimidization reaction, i.e., a dehydration ring-closing reaction, with the (a3) component at about 60 to 250°C, preferably 80 to 200°C, for about 0.5 to 30 hours, preferably 0.5 to 10 hours, to obtain the desired (A) component.
[0026] In addition, in the imidization reaction or maleimidization reaction, various known reaction catalysts, dehydrating agents, and organic solvents described later can be used. Examples of reaction catalysts include aliphatic tertiary amines such as triethylamine, aromatic tertiary amines such as dimethylaniline, heterocyclic tertiary amines such as pyridine, picoline, isoquinoline, and organic acids such as methanesulfonic acid and paratoluenesulfonic acid monohydrate. These can be used alone or in combination of two or more. Examples of dehydrating agents include aliphatic acid anhydrides such as acetic anhydride, and aromatic acid anhydrides such as benzoic anhydride. These can be used alone or in combination of two or more.
[0027] In addition, the component (A) can be purified by various known methods to increase its purity. For example, first, the component (A) dissolved in an organic solvent and pure water are placed in a separatory funnel. The separatory funnel is then shaken and allowed to stand. After the aqueous layer and the organic layer are separated, only the organic layer is collected, thereby purifying the component (A).
[0028] The molecular weight of the (A) component can be controlled by the number of moles of the (a1) component and the (a2) component, and the smaller the number of moles of the (a1) component is compared with the number of moles of the (a2) component, the smaller the molecular weight can be. For the purpose of easily achieving the effects of the present invention, the ratio of [the number of moles of the (a1) component] / [the number of moles of the (a2) component] is usually about 0.30 to 0.85, preferably 0.50 to 0.80.
[0029] From the viewpoint of solubility in solvents and heat resistance, the molecular weight of the (A) component is preferably a weight average molecular weight of 3000 to 25000, and more preferably 7000 to 20000. If the weight average molecular weight is 25000 or less, the solubility in organic solvents is good, and if it is 3000 or more, the effect of improving heat resistance tends to be sufficiently obtained.
[0030] The component (A) of the present embodiment may be a commercially available compound, and specifically, for example, BMI-3000CG (synthesized from dimer diamine, pyromellitic dianhydride, and maleic anhydride), BMI-1500, BMI-1700, BMI-5000, etc. manufactured by DESIGNER MOLECURES Inc. may be suitably used. The component (A) may be used alone or in combination of two or more kinds.
[0031] ((B) Component: Inorganic filler) As the (B) component, various known inorganic fillers that can be used in bismaleimide adhesive compositions can be used without any particular limitation. Examples of the (B) component include aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, boron nitride, silica, graphite powder, boehmite, etc. Among these, silica is particularly preferred because of its excellent low dielectric tangent. The (B) component can be used alone or in combination of two or more.
[0032] The average particle size of component (B) may be 50 nm or more, 100 nm or more, or 200 nm or more, and may be 10 μm or less, 5.0 μm or less, 3.0 μm or less, or 1.0 μm or less. The average particle size of component (B) is preferably 100 nm to 10 μm or 50 nm to 5.0 μm, more preferably 100 nm to 3.0 μm, and even more preferably 200 nm to 1.0 μm. When the average particle size of component (B) is within the above range, the surface roughness of the adhesive sheet can be reduced, and the adhesion to substrates such as polyimide films and copper foils can be increased.
[0033] The average particle size of the component (B) is determined by the median diameter (d50) at 50% of the cumulative particle size in the volume cumulative particle size distribution. The average particle size can be measured using a laser diffraction scattering type particle size distribution measuring device.
[0034] The (B) component is preferably surface-treated, preferably with a coupling agent, more preferably with a silane coupling agent. By surface-treating the (B) component, not only can the (B) component be more easily dispersed in an organic solvent, but also the surface roughness of the adhesive sheet can be further reduced, and the adhesiveness to substrates such as polyimide films and copper foils can be improved.
[0035] The above-mentioned coupling agents include silane coupling agents, titanium coupling agents, and aluminum coupling agents. The above-mentioned silane coupling agents include methacrylsilane, acrylic silane, aminosilane, phenylaminosilane, imidazole silane, phenylsilane, vinylsilane, and epoxysilane. These can be used alone or in combination of two or more.
[0036] The content of component (B) is 5 to 55% by mass, preferably 5 to 50% by mass, and more preferably 5 to 25% by mass or 10 to 35% by mass, based on the total amount of solids (non-volatile content) of the adhesive composition (100% by mass). When the content of component (B) is 55% by mass or less, there is a tendency that a decrease in adhesiveness can be suppressed, and when it is 5% by mass or more, there is a tendency that the effect of reducing the dielectric tangent and the effect of improving heat resistance can be sufficiently obtained.
[0037] (Component (C): organic solvent) The component (C) is not particularly limited as long as it dissolves the component (A). As the component (C), for example, aromatic hydrocarbons such as benzene, toluene, xylene, mesitylene, etc., alcohol-based solvents such as methanol, ethanol, isopropyl alcohol, butanol, pentanol, hexanol, propanediol, phenol, etc., ketone-based solvents such as acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanone, hexanone, cyclopentanone, cyclohexanone, isophorone, acetophenone, etc., cellosolves such as methyl cellosolve, ethyl cellosolve, etc., ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, methyl propionate, butyl formate, etc., glycol ether-based solvents such as ethylene glycol mono-n-butyl ether, ethylene glycol mono-iso-butyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol mono-iso-butyl ether, triethylene glycol mono-n-butyl ether, tetraethylene glycol mono-n-butyl ether, etc., can be used alone or in combination of two or more of these. In a preferred embodiment, the aromatic hydrocarbon toluene or mesitylene, which has high solubility for component (A), is used in combination with the ketone solvent methyl ethyl ketone or methyl isobutyl ketone, which has high dispersibility for component (B).
[0038] The amount of component (C) used is not particularly limited, but it is usually sufficient to use it in such a range that the nonvolatile content of the adhesive composition of the present embodiment is about 20 to 65 mass %.
[0039] (Component (D): Polymerization initiator) Specific examples of the (D) component include organic peroxides, imidazole compounds, phosphine compounds, and phosphonium salt compounds. These can be used alone or in combination of two or more. Among them, imidazole compounds are particularly preferred because they have excellent functions as polymerization initiators and are also excellent in terms of low dielectric properties.
[0040] Examples of organic peroxides include methyl ethyl ketone peroxide, methylcyclohexanone peroxide, methylacetoacetate peroxide, acetylacetone peroxide, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(4,4-di-t-butylperoxy)cyclohexane, n-butyl 4,4-bis(t-butylperoxy)valerate, 2,2-bis(t-butylperoxy)butane, 1,1-bis(t-butylperoxy)-2-methylcyclohexane, t-butyl hydroperoxide, p-menthane hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-hexyl hydroperoxide, dicumyl peroxide, 2,5-dimethyl-2 ,5-bis(t-butylperoxy)hexane, α,α'-bis(t-butylperoxy)diisopropylbenzene, t-butylcumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, isobutyryl peroxide, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, cinnamic acid peroxide, m-toluoyl peroxide, benzoyl peroxide, diisopropyl peroxide -oxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di(3-methyl-3-methoxybutyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, cumyl peroxyneodecanoate, 1,1,3,3,-Tetramethylbutylperoxyneodecanoate, 1-cyclohexyl-1-methylethylperoxyneodecanoate, t-hexylperoxyneodecanoate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 1-cyclohexyl-1-methylethylperoxy-2-ethylhexanoate, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyisobutyrate, t-butyl Examples of the peroxymaleic acid include peroxymaleic acid, t-butylperoxylaurate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl monocarbonate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, t-butylperoxyacetate, t-hexylperoxybenzoate, t-butylperoxy-m-toluoyl benzoate, t-butylperoxybenzoate, bis(t-butylperoxy)isophthalate, t-butylperoxyallyl monocarbonate, and 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone. These may be used alone or in combination of two or more. Among these organic peroxides, dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, α,α'-bis(t-butylperoxy)diisopropylbenzene, etc. are preferred.
[0041] Examples of the imidazole compound include 2-ethyl-4-methylimidazole, 2-methylimidazole, 2-ethylimidazole, 2,4-dimethylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 1-vinyl-2-methylimidazole, 1-propyl-2-methylimidazole, 2-isopropylimidazole, 1-cyanomethyl-2-methyl-imidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, and 1-cyanoethyl-2-phenylimidazole. Among these, 1-cyanoethyl-2-phenylimidazole and 2-ethyl-4-methylimidazole are preferred because they have high solubility in the adhesive composition of the present embodiment. These may be used alone or in combination of two or more.
[0042] Examples of the phosphine compound include primary phosphines, secondary phosphines, and tertiary phosphines. Specific examples of the primary phosphines include alkyl phosphines such as ethylphosphine and propylphosphine, and phenylphosphine. Specific examples of the secondary phosphines include dialkyl phosphines such as dimethylphosphine and diethylphosphine, and secondary phosphines such as diphenylphosphine, methylphenylphosphine, and ethylphenylphosphine. Specific examples of the tertiary phosphines include trialkyl phosphines such as trimethylphosphine, triethylphosphine, tributylphosphine, and trioctylphosphine, tricyclohexylphosphine, triphenylphosphine, alkyldiphenylphosphine, dialkylphenylphosphine, tribenzylphosphine, tritolylphosphine, tri-p-styrylphosphine, tris(2,6-dimethoxyphenyl)phosphine, tri-4-methylphenylphosphine, tri-4-methoxyphenylphosphine, and tri-2-cyanoethylphosphine. Among these, tertiary phosphines are preferably used. These can be used alone or in combination of two or more.
[0043] Examples of the phosphonium salt compound include compounds having tetraphenylphosphonium salt, alkyltriphenylphosphonium salt, tetraalkylphosphonium, etc., and specific examples thereof include tetraphenylphosphonium-thiocyanate, tetraphenylphosphonium-tetra-p-methylphenylborate, butyltriphenylphosphonium-thiocyanate, tetraphenylphosphonium-phthalic acid, tetrabutylphosphonium-1,2-cyclohexyldicarboxylic acid, tetrabutylphosphonium-1,2-cyclohexyldicarboxylic acid, tetrabutylphosphonium-lauric acid, etc. These may be used alone or in combination of two or more.
[0044] The content of the (D) component is not particularly limited, but is preferably 0.1 to 10.0 parts by mass, and more preferably 1.0 to 5.0 parts by mass, per 100 parts by mass of the (A) component.
[0045] The adhesive composition of the present embodiment is prepared according to a commonly used method. Examples of the preparation method include melt mixing, powder mixing, and solution mixing. In addition, in this case, other than the essential components of the present embodiment, for example, a release agent, a flame retardant, an ion trapping agent, an antioxidant, an adhesion promoter, a stress reducing agent, a colorant, a coupling agent, etc. may be blended within a range that does not impair the effects of the present invention. In addition, the adhesive composition of the present embodiment may contain a resin other than the above component (A), such as an epoxy resin, an acrylate compound, a vinyl compound, a benzoxazine compound, or a bismaleimide compound.
[0046] (Release agent) The mold release agent is added to improve the releasability from the mold. As the mold release agent, any of the known ones can be used, such as carnauba wax, rice wax, candelilla wax, polyethylene, polyethylene oxide, polypropylene, montanic acid, montan wax which is an ester compound of montanic acid with saturated alcohol, 2-(2-hydroxyethylamino)ethanol, ethylene glycol, glycerin, etc., stearic acid, stearic acid ester, stearic acid amide, etc. These can be used alone or in combination of two or more.
[0047] (Flame retardant) The flame retardant is added to provide flame retardancy, and can be any known flame retardant, and is not particularly limited. Examples of the flame retardant include phosphazene compounds, silicon compounds, zinc molybdate-supported talc, zinc molybdate-supported zinc oxide, aluminum hydroxide, magnesium hydroxide, molybdenum oxide, etc. These can be used alone or in combination of two or more.
[0048] (Ion trapping agent) The ion trapping agent is added to capture ion impurities contained in the liquid resin composition and prevent thermal deterioration and moisture absorption deterioration. Any known ion trapping agent can be used, and is not particularly limited. Examples of the ion trapping agent include hydrotalcites, bismuth hydroxide compounds, and rare earth oxides. These can be used alone or in combination of two or more.
[0049] <Cured product> The cured product of the present embodiment is obtained by curing the adhesive composition of the present embodiment, and specifically, can be obtained by heat treating the adhesive composition at about 150 to 250° C. for about 5 minutes to 3 hours.
[0050] The shape of the cured product of the present embodiment is not particularly limited, but when used for adhering substrate sheets, the cured product can be in the form of a sheet having a thickness of usually about 1 to 100 μm, and preferably about 3 to 50 μm, and the thickness can be appropriately adjusted depending on the application.
[0051] <Adhesive sheet> The adhesive sheet of this embodiment is obtained by applying the adhesive composition of this embodiment to a sheet substrate and drying it. Examples of the sheet substrate include organic substrates such as polyimide, polyimide-silica hybrid, polyamide, polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polymethyl methacrylate resin (PMMA), polystyrene resin (PSt), polycarbonate resin (PC), acrylonitrile-butadiene-styrene resin (ABS), ethylene terephthalate, phenol, phthalic acid, aromatic polyester resin obtained from hydroxynaphthoic acid and parahydroxybenzoic acid (so-called liquid crystal polymer; manufactured by Kuraray Co., Ltd., "Vexstar", etc.), and among these, polyimide film, particularly polyimide-silica hybrid film, is preferred from the viewpoints of heat resistance and dimensional stability. The thickness of the sheet substrate can be appropriately set depending on the application.
[0052] <Laminate> The laminate of this embodiment is obtained by further thermocompression bonding a sheet substrate to the adhesive surface of the adhesive sheet. The sheet substrate is preferably made of glass, iron, aluminum, 42 alloy, copper or other metal, ITO, silicon, silicon carbide or other inorganic substrate, and the thickness can be appropriately set according to the application. The laminate may be further heat-treated.
[0053] <Flexible printed circuit boards and flexible printed wiring boards> The flexible printed circuit board of this embodiment uses the laminate, and is obtained by further laminating the adhesive surface of the adhesive sheet to the inorganic substrate surface of the laminate. The flexible printed circuit board is preferably one using a polyimide film as the organic substrate and a metal foil (particularly copper foil) as the inorganic substrate. The metal surface of the flexible printed circuit board is then soft-etched to form a circuit, and the adhesive sheet is then laminated thereon and heat-pressed to obtain a flexible printed wiring board. EXAMPLES
[0054] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited thereto. In each example, parts and % are by weight unless otherwise specified.
[0055] <Production Example 1> Into a 1L flask equipped with a cooler, a nitrogen inlet tube, a thermocouple, and a stirrer, 52.8 parts by mass of pyromellitic anhydride (manufactured by Daicel Corporation), 432.5 parts by mass of mesitylene (manufactured by Toyo Gosei Co., Ltd.), and 94.0 parts by mass of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) were added. After the addition, the temperature was raised to 80°C, and the temperature was maintained for 0.5 hours, and 176.7 parts by mass of dimer diamine (trade name "PRIAMINE1075", manufactured by Croda Japan Co., Ltd.) was added dropwise. After the dropwise addition, 3.7 parts by mass of methanesulfonic acid (manufactured by Wako Pure Chemical Industries, Ltd.) was added. The temperature was then raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 1 hour, and the water and ethanol in the reaction solution were removed to obtain an intermediate polyimide resin. Subsequently, the obtained polyimide resin was cooled to 130°C, 23.4 parts by mass of maleic anhydride (manufactured by Fuso Chemical Co., Ltd.) was added, the temperature was raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 4 hours to remove water from the reaction liquid, thereby obtaining a bismaleimide resin.
[0056] The obtained bismaleimide resin was placed in a separatory funnel, 1000 parts by mass of pure water was added, the separatory funnel was shaken, and the mixture was allowed to stand. After standing, the aqueous layer and the organic layer were separated, and only the organic layer was collected. The collected organic layer was placed in a 1L glass container equipped with a cooler, a nitrogen inlet tube, a thermocouple, a stirrer, and a vacuum pump, and the temperature was raised to 88-93°C. After removing the water, the temperature was raised to 130°C, and the solvent was removed for 1 hour under a reduced pressure of -0.1 MPa. After removing the solvent, the mixture was cooled to 100°C and brought to normal pressure, and then 135.9 parts by mass of toluene (manufactured by Yamaichi Chemical Industry Co., Ltd.) was added to obtain a solution of bismaleimide resin (A-1) (non-volatile content of 59.8% by mass).
[0057] <Production Example 2> Into a reaction vessel similar to that of Production Example 1, 66.7 parts by mass of 4,4'-oxydiphthalic anhydride (manufactured by Wako Pure Chemical Industries, Ltd.), 426.0 parts by mass of mesitylene (manufactured by Toyo Gosei Co., Ltd.), and 91.2 parts by mass of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) were added. After the addition, the temperature was raised to 80°C, and the temperature was maintained for 0.5 hours, and 159.0 parts by mass of dimer diamine (trade name "PRIAMINE1075", manufactured by Croda Japan Co., Ltd.) was added dropwise. After the dropwise addition, 3.3 parts by mass of methanesulfonic acid (manufactured by Wako Pure Chemical Industries, Ltd.) was added. The temperature was then raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 1 hour, and the water and ethanol in the reaction liquid were removed to obtain an intermediate polyimide resin. Subsequently, the obtained polyimide resin was cooled to 130°C, 21.1 parts by mass of maleic anhydride (manufactured by Fuso Chemical Co., Ltd.) was added, the temperature was raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 4 hours, and water in the reaction liquid was removed to obtain a bismaleimide resin.
[0058] The obtained bismaleimide resin was placed in a separatory funnel, 1000 parts by mass of pure water was added, the separatory funnel was shaken, and the mixture was allowed to stand. After standing, the aqueous layer and the organic layer were separated, and only the organic layer was collected. The collected organic layer was placed in a 1L glass container equipped with a cooler, a nitrogen inlet tube, a thermocouple, a stirrer, and a vacuum pump, and the temperature was raised to 88-93°C. After removing the water, the temperature was raised to 150°C and the solvent was removed for 1 hour under a reduced pressure of -0.1MPa. After removing the solvent, the mixture was cooled to 100°C and brought to normal pressure, and then 122.3 parts by mass of toluene (manufactured by Yamaichi Chemical Industry Co., Ltd.) was added to obtain a solution of bismaleimide resin (A-2) (non-volatile content of 59.9% by mass).
[0059] <Production Example 3> Into a reaction vessel similar to that of Production Example 1, 63.2 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (manufactured by Wako Pure Chemical Industries, Ltd.), 419.6 parts by mass of mesitylene (manufactured by Toyo Gosei Co., Ltd.), and 90.1 parts by mass of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) were added. After the addition, the temperature was raised to 80°C, and the temperature was maintained for 0.5 hours, and 159.0 parts by mass of dimer diamine (trade name "PRIAMINE1075", manufactured by Croda Japan Co., Ltd.) was added dropwise. After the dropwise addition, 3.3 parts by mass of methanesulfonic acid (manufactured by Wako Pure Chemical Industries, Ltd.) was added. The temperature was then raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 1 hour, and the water and ethanol in the reaction liquid were removed to obtain an intermediate polyimide resin. Subsequently, the obtained polyimide resin was cooled to 130°C, 21.1 parts by mass of maleic anhydride (manufactured by Fuso Chemical Co., Ltd.) was added, the temperature was raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 4 hours, and water in the reaction liquid was removed to obtain a bismaleimide resin.
[0060] The obtained bismaleimide resin was placed in a separatory funnel, 1000 parts by mass of pure water was added, the separatory funnel was shaken, and the mixture was allowed to stand. After standing, the aqueous layer and the organic layer were separated, and only the organic layer was collected. The collected organic layer was placed in a 1L glass container equipped with a cooler, a nitrogen inlet tube, a thermocouple, a stirrer, and a vacuum pump, and the temperature was raised to 88-93°C. After removing the water, the temperature was raised to 150°C and the solvent was removed for 1 hour under a reduced pressure of -0.1MPa. After removing the solvent, the mixture was cooled to 100°C and brought to normal pressure, and then 120.5 parts by mass of toluene (manufactured by Yamaichi Chemical Industry Co., Ltd.) was added to obtain a solution of bismaleimide resin (A-3) (non-volatile content of 59.3% by mass).
[0061] <Production Example 4> Into a reaction vessel similar to that of Production Example 1, 91.0 parts by mass of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride (trade name "BISDA1000", manufactured by SABIC Innovative Plastics Japan, LLC), 415.3 parts by mass of mesitylene (manufactured by Toyo Gosei Co., Ltd.), and 86.7 parts by mass of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) were added. After the addition, the temperature was raised to 80°C, the temperature was maintained for 0.5 hours, and 129.6 parts by mass of dimer diamine (trade name "PRIAMINE1075", manufactured by Croda Japan Co., Ltd.) was added dropwise. After the dropwise addition, 2.7 parts by mass of methanesulfonic acid (manufactured by Wako Pure Chemical Industries, Ltd.) was added. The temperature was then raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 1 hour, and the water and ethanol in the reaction liquid were removed to obtain an intermediate polyimide resin. Subsequently, the obtained polyimide resin was cooled to 130°C, 17.2 parts by mass of maleic anhydride (manufactured by Fuso Chemical Co., Ltd.) was added, the temperature was raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 4 hours to remove water from the reaction liquid, thereby obtaining a bismaleimide resin.
[0062] The obtained bismaleimide resin was placed in a separatory funnel, 1000 parts by mass of pure water was added, the separatory funnel was shaken, and the mixture was allowed to stand. After standing, the aqueous layer and the organic layer were separated, and only the organic layer was collected. The collected organic layer was placed in a 1L glass container equipped with a cooler, a nitrogen inlet tube, a thermocouple, a stirrer, and a vacuum pump, and the temperature was raised to 88-93°C. After removing the water, the temperature was raised to 150°C and the solvent was removed for 1 hour under a reduced pressure of -0.1MPa. After removing the solvent, the mixture was cooled to 100°C and brought to normal pressure, and then 119.3 parts by mass of toluene (manufactured by Yamaichi Chemical Industry Co., Ltd.) was added to obtain a solution of bismaleimide resin (A-4) (non-volatile content of 59.5% by mass).
[0063] <Comparative Manufacturing Example 1> Into a reaction vessel similar to that of Production Example 1, 36.5 parts by mass of pyromellitic anhydride (manufactured by Daicel Corporation), 429.0 parts by mass of mesitylene (manufactured by Toyo Gosei Co., Ltd.), and 88.7 parts by mass of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) were added. After the addition, the temperature was raised to 80°C, and the temperature was maintained for 0.5 hours, and 191.6 parts by mass of α,ω-bis(3-aminopropyl)polydimethylsiloxane (trade name "KF-8010", manufactured by Shin-Etsu Chemical Co., Ltd.) was added dropwise. After the dropwise addition, 2.6 parts by mass of methanesulfonic acid (manufactured by Wako Pure Chemical Industries, Ltd.) was added. The temperature was then raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 1 hour, and the water and ethanol in the reaction liquid were removed to obtain an intermediate polyimide resin. Subsequently, the obtained polyimide resin was cooled to 130°C, 16.4 parts by mass of maleic anhydride (manufactured by Fuso Chemical Co., Ltd.) was added, the temperature was raised to 165°C, and a dehydration ring-closing reaction was carried out at 165°C for 4 hours to remove water from the reaction liquid, thereby obtaining a bismaleimide resin.
[0064] The obtained bismaleimide resin was placed in a separatory funnel, 1000 parts by mass of pure water was added, the separatory funnel was shaken, and the mixture was allowed to stand. After standing, the aqueous layer and the organic layer were separated, and only the organic layer was collected. The collected organic layer was placed in a 1L glass container equipped with a cooler, a nitrogen inlet tube, a thermocouple, a stirrer, and a vacuum pump, and the temperature was raised to 88-93°C. After removing the water, the temperature was raised to 150°C, and the solvent was removed for 1 hour under a reduced pressure of -0.1 MPa. After removing the solvent, the mixture was cooled to 100°C and brought to normal pressure, and then 123.2 parts by mass of toluene (manufactured by Yamaichi Chemical Industry Co., Ltd.) was added to obtain a solution of bismaleimide resin (X) (non-volatile content of 59.7% by mass).
[0065] [Table 1]
[0066] PMDA: Pyromellitic dianhydride ODPA: 4,4'-oxydiphthalic anhydride BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride BISDA: 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride PRIAMINE: Dimer diamine KF8010: α,ω-bis(3-aminopropyl)polydimethylsiloxane
[0067] <Physical property evaluation method> (Weight average molecular weight (Mw)) The weight average molecular weight (Mw) was measured by GPC (gel permeation chromatography). A sample in which bismaleimide resin was dissolved in tetrahydrofuran (THF) to a concentration of 3% by mass was injected in an amount of 50 μL into a column (GL-R420 (Hitachi High-Tech Fielding Corporation) x 1, GL-R430 (Hitachi High-Tech Fielding Corporation) x 1, GL-R440 (Hitachi High-Tech Fielding Corporation) x 1) heated to 30 ° C., and the measurement was performed using THF as a developing solvent and a flow rate of 1.6 mL / min. The detector used was an L-3350 RI detector (Hitachi, Ltd.), and the weight average molecular weight (Mw) was converted from the elution time using a molecular weight / elution time curve prepared using standard polystyrene (Tosoh Corporation).
[0068] [Example 1] In a 225 ml cylindrical container, 100 parts by mass of the bismaleimide resin (A-1) solution obtained in Production Example 1, 21.4 parts by mass of a silica-containing slurry (manufactured by Admatechs Co., Ltd., product name "SC2050-KNK", silica 70% by mass) as component (B), and 20.0 parts by mass of methyl isobutyl ketone (manufactured by Wako Pure Chemical Industries, Ltd.) as component (C) were charged. The container was then covered, and the mixture in the container was stirred at 70 rpm for 4 hours or more using a variable mix rotor (manufactured by AS ONE Co., Ltd., product number "VMR-5R") to obtain an adhesive composition with a non-volatile content of 52.9% by mass.
[0069] [Examples 2 to 8] Each adhesive composition was obtained in the same manner as in Example 1, except that the types of components (A), (B), (C), and (D) shown in Table 2 were used in the amounts shown in the same table.
[0070] [Comparative Example 1] An adhesive composition was obtained in the same manner as in Example 1, except that the solution of component (X) was used in the amount shown in Table 2 instead of the solution of component (A-1) in Example 1, and the types of components (B) and (C) shown in Table 2 were used in the amounts shown in the same table.
[0071] [Comparative Example 2] An adhesive composition was obtained in the same manner as in Example 1, except that the amount of component (B) used was changed to the amount shown in Table 2.
[0072] [Table 2]
[0073] SC2050-KNK: Silica-containing slurry (manufactured by Admatechs Co., Ltd., 70% silica by mass, silica particles surface-treated with phenylaminosilane, average particle size 0.4 μm) MIBK: Methyl isobutyl ketone (Wako Pure Chemical Industries, Ltd.) 2E4MZ: 2-ethyl-4-methylimidazole (Wako Pure Chemical Industries, Ltd.)
[0074] Example 9 In a 225 ml cylindrical container, 100 parts by mass of the bismaleimide resin (A-1) solution obtained in Production Example 1, 42.7 parts by mass of silica-containing slurry (manufactured by Admatechs Co., Ltd., product name "SC2050-KNK", silica 70% by mass) as component (B), and 25.0 parts by mass of methyl isobutyl ketone (manufactured by Wako Pure Chemical Industries, Ltd.) as component (C) were charged, and stirred at 9000 rpm for 20 minutes using a homomixer (manufactured by Primix Co., Ltd., "TK homomixer MARKII") Then, 0.60 parts by mass of dicumyl peroxide (manufactured by NOF Corp., product name "Percumyl D") as component (D) was added, and the mixture was stirred at 70 rpm for 1 hour or more using a variable mix rotor (manufactured by AS ONE Co., Ltd., product number "VMR-5R") to obtain an adhesive composition with a non-volatile content of 53.6% by mass.
[0075] [Examples 10 to 19] Each adhesive composition was obtained in the same manner as in Example 9, except that the types of components (A), (B), (C), and (D) shown in Table 3 were used in the amounts shown in the same table.
[0076] [Table 3]
[0077] 3SX-CX1: Silica-containing slurry (manufactured by Admatechs Co., Ltd., 60.5% by mass silica, silica particles surface-treated with phenylaminosilane, average particle size 0.3 μm) YA050C-KJK: Silica-containing slurry (manufactured by Admatechs Co., Ltd., 51.0% by mass of silica, silica particles surface-treated with phenylaminosilane, average particle size 50 nm) DCP: Dicumyl peroxide (NOF Corporation)
[0078] <Preparation of adhesive sheet (1)> The adhesive composition of Example 1 was applied using an applicator onto Filmbina (registered trademark) (PET film, Fujimori Kogyo Co., Ltd., product name "NS14", film thickness 75 μm) so as to have a thickness of 30 μm after drying, and dried in an oven at 130° C. for 20 minutes to produce an adhesive sheet (1). Adhesive sheets (1) were obtained in the same manner for the adhesive compositions of the other Examples and Comparative Examples.
[0079] <Preparation of hardened sheet (1)> A polyimide film (product name "100EN", manufactured by DuPont-Toray Co., Ltd., film thickness 25 μm) was superimposed on the adhesive surface of the adhesive sheet (1) of Example 1, and thermocompression bonded using a vacuum laminator at 75°C, 0.5 MPa, and 30 seconds. After thermocompression bonding, the PET film was peeled off, and a heat treatment was carried out in a hot air dryer at 200°C for 2 hours to obtain a cured sheet (1). Cured sheets (1) were obtained in the same manner for the adhesive compositions of the other Examples and Comparative Examples.
[0080] <Preparation of hardened sheet (2)> The adhesive composition of Example 1 was applied using an applicator onto Separium (manufactured by Toyo Aluminum K.K., product name "50B2-EA(A)4G / M2", film thickness 50 μm) so as to have a thickness of 100 μm after drying, and dried in an oven at 130° C. for 20 minutes. Thereafter, a heat treatment was performed in an oven at 200° C. for 1 hour. After the heat treatment, the sheet was cooled to room temperature and peeled off from the Separium to obtain a cured sheet (2).
[0081] <Preparation of Laminate (1)> The adhesive sheet (1) of Example 1 from which the PET film had been peeled off was laminated with two sheets of copper foil (product name "F2WS-18", manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) so that the roughened surface of the copper foil faced the adhesive sheet, and was thermocompressed in a hot press at 200° C., 2 MPa, and 2 hours to obtain a laminate (1) in which the copper foil, the cured adhesive sheet, and the copper foil were laminated in that order. Laminates (1) were obtained in the same manner for the adhesive compositions of the other Examples and Comparative Examples.
[0082] <Preparation of Laminate (2)> The adhesive sheet (1) from Example 1 from which the PET film had been peeled off was laminated with two polyimide films (product name "100EN", manufactured by DuPont-Toray Co., Ltd., thickness 25 μm) so that the adhesive sheet was in the middle, and then thermocompression-bonded under conditions of 200°C, 2 MPa, and 2 hours in a heat press to obtain a laminate (2) in which a polyimide film, a cured product of the adhesive sheet, and a polyimide film were laminated in that order. Laminates (2) were obtained in the same manner for the adhesive compositions of the other Examples and Comparative Examples.
[0083] <Evaluation of tackiness> The shiny side of copper foil (product name "F2WS-18", Furukawa Electric Co., Ltd., thickness 18 μm) was placed on the adhesive side of the cured sheet (1), and the copper foil was moved horizontally. If the copper foil was sticky and could not be moved, it was judged to have tackiness, and if it could be moved horizontally, it was judged to have no tackiness.
[0084] <Adhesive strength> The adhesive strength between the polyimide film and the copper foil was measured using the laminate (1) and the laminate (2). The adhesive strength was measured at room temperature and at a tensile speed of 5 mm / s using a 90° peel tester (manufactured by Yamaden Co., Ltd., RHEONERII CREEP METER RE2-3305B). The results are shown in Tables 4 and 5.
[0085] <Adhesive strength evaluation criteria> A: Adhesive strength is 1.0 kN / m or more B: Adhesive strength is 0.5 kN / m or more and less than 1.0 kN / m C: Adhesive strength is less than 0.5 kN / m
[0086] <Dielectric constant and dielectric loss tangent> The copper foils on both sides of the laminate (1) were removed by etching, and the laminate was dried at 130°C for 30 minutes. Then, a test piece of 10 cm x 5 cm was prepared, and the relative dielectric constant and dielectric loss tangent at 10 GHz were measured using an SPDR dielectric resonator (manufactured by Agilent Technologies). The results are shown in Tables 4 and 5. Note that, for Comparative Example 1, it was difficult to prepare a test piece by etching, so measurements could not be made.
[0087] <5% weight loss temperature> The copper foil on both sides of the laminate (1) was removed by etching, and the laminate was dried at 130°C for 30 minutes. Then, 6.0 to 10.0 mg of the cured adhesive sheet was weighed out in an open-type sample container (Seiko Denshi Co., Ltd., "P / N SSC000E030") and measured under conditions of a nitrogen flow rate of 300 mL / min and a heating rate of 10°C / min to measure the 5% weight loss temperature (Td5). The measuring device used was a TG / DTA7200 (Hitachi High-Tech Science Co., Ltd.). The results are shown in Tables 4 and 5.
[0088] <Coefficient of linear expansion (CTE) α 1 , α 2 > A test piece having a size of 30 mm x 4 mm was prepared from the cured sheet (2). The test piece was used to measure the coefficient of linear expansion (CTE) using a thermomechanical analyzer (product name "TMA / SS7100", manufactured by Hitachi High-Tech Science Corporation). The measurement mode was tensile mode, the measurement load was 20 to 49 mN, the measurement atmosphere was air, the heating rate was 10°C / min for the first run and 5°C / min for the second run, and the measurement result at 40 to 55°C for the second run was expressed as α 1 The measurement results at 110 to 160°C are shown as α 2 The results are shown in Tables 4 and 5.
[0089] [Table 4]
[0090] [Table 5]
[0091] As is clear from Tables 4 and 5, it was confirmed that the adhesive compositions (Examples) containing the bismaleimide resin (A) of this embodiment and the inorganic filler (B) and having a content of the inorganic filler (B) within the range of 5 to 55 mass % (based on the total solid content of the adhesive composition) not only have excellent low dielectric properties, but also exhibit high adhesive strength with copper foil and polyimide film. Furthermore, it was confirmed that the cured products obtained using the adhesive compositions of the Examples have low tack, high 5% weight loss temperatures, and low outgassing. Furthermore, it was confirmed that the cured products obtained using the adhesive compositions of the Examples have a reduced coefficient of linear expansion (CTE). Note that in Examples 14 to 19, the dielectric properties are comparable to those of the other Examples. [Industrial Applicability]
[0092] The adhesive composition of the present invention not only has excellent low dielectric properties in the high frequency band, but also has excellent adhesion to substrates such as copper foils and polyimide sheets. In addition, the cured product (adhesive layer) obtained from the adhesive composition has low tack, a high 5% weight loss temperature, little outgassing, and a low coefficient of linear expansion (CTE), and is therefore useful not only as an adhesive used in the manufacture of printed circuit boards (build-up boards, flexible printed wiring boards, etc.) and copper-clad boards for flexible printed wiring boards, but also as an electrical insulating material such as a semiconductor interlayer material, a coating agent, a resist ink, and a conductive paste.
Claims
1. The present invention comprises a bismaleimide resin (A) obtained by reacting an aromatic tetracarboxylic acid (a1), a dimer diamine (a2), and maleic anhydride (a3), and an inorganic filler (B), The weight average molecular weight of the bismaleimide resin (A) is 7,000 to 25,000, A bismaleimide-based adhesive composition, wherein the content of the inorganic filler (B) is 10 to 55 mass % based on the total solid content of the adhesive composition.
2. The present invention comprises a bismaleimide resin (A) obtained by reacting an aromatic tetracarboxylic acid (a1), a dimer diamine (a2), and maleic anhydride (a3), and an inorganic filler (B), The weight average molecular weight of the bismaleimide resin (A) is 7,000 to 25,000, A bismaleimide-based adhesive composition (excluding those containing a thermoplastic resin), wherein the content of the inorganic filler (B) is 5 to 55 mass % based on the total solid content of the adhesive composition.
3. 3. The bismaleimide adhesive composition according to claim 1, wherein the aromatic tetracarboxylic acid (a1) is pyromellitic anhydride or a compound represented by the following general formula (1): 【Chemistry 1】 [In formula (1), X represents a single bond or at least one group selected from the following group.] 【Chemistry 2】
4. The bismaleimide adhesive composition according to any one of claims 1 to 3, wherein the dimer diamine (a2) is a compound represented by the following general formula (2) and / or general formula (2'): 【Chemistry 3】 【Chemistry 4】 [In formulas (2) and (2'), m, n, p, and q each represent an integer of 1 or more selected such that m+n=6 to 17, and p+q=8 to 19, and the bond shown by the dashed line represents a carbon-carbon single bond or a carbon-carbon double bond. However, when the bond shown by the dashed line is a carbon-carbon double bond, formulas (2) and (2') have a structure in which the number of hydrogen atoms bonded to each carbon atom constituting the carbon-carbon double bond is reduced by one from the number shown in formulas (2) and (2')]
5. The bismaleimide adhesive composition according to any one of claims 1 to 4, wherein the inorganic filler is silica.
6. The bismaleimide adhesive composition according to any one of claims 1 to 5, further comprising a polymerization initiator (D).
7. 7. The bismaleimide adhesive composition according to claim 6, wherein the polymerization initiator (D) is at least one selected from the group consisting of organic peroxides, imidazole compounds, phosphine compounds, and phosphonium salt compounds.
8. 7. The bismaleimide adhesive composition according to claim 6, wherein the polymerization initiator (D) is at least one selected from the group consisting of imidazole compounds, phosphine compounds, and phosphonium salt compounds.
9. The bismaleimide adhesive composition according to any one of claims 1 to 8, wherein the inorganic filler (B) has an average particle size of 100 nm to 10 µm.
10. The bismaleimide adhesive composition according to any one of claims 1 to 9, wherein the inorganic filler (B) has an average particle size of 200 nm to 1.0 µm.
11. The bismaleimide-based adhesive composition according to any one of claims 1 to 10, wherein the content of the inorganic filler (B) is 5 to 25 mass% based on the total solid content of the adhesive composition.
12. A cured product obtained by curing the bismaleimide adhesive composition according to any one of claims 1 to 11.
13. An adhesive sheet obtained by applying the bismaleimide adhesive composition according to any one of claims 1 to 11 to a sheet substrate and drying it.
14. A laminate obtained by further thermocompression bonding a sheet substrate to the adhesive surface of the adhesive sheet according to claim 13.
15. A laminate obtained by further heating the laminate according to claim 14.
16. A flexible printed wiring board comprising the laminate according to claim 15.
Citation Information
Patent Citations
Insulating material and laminated structure body
JP2012229319A
Flame-retardant resin composition and copper foil with resin
JP2018044065A
Cured body, resin material and multilayer printed board
JP2019173009A
Adhesive composition, laminate, and adhesive sheet
JP2020012026A
Thermosetting resin composition
JP2020045446A